Did the Scribe of P52 use the Nomina Sacra? Another Look - Hill, Charles E. (New Testament studies, 2002)
Recently, Christopher M. Tuckett offered in this journal a careful and incisive study of the question whether the scribe of P52 (PRyl 457) employed the nomina sacra forms. The extant text contains no words that were commonly abbreviated as such, though missing portions of the fragment would have contained three instances (lines 2, 5, 7) of the name ‘Jesus’. Tuckett concluded with C. H. Roberts's original opinion (later changed) that the abbreviations were probably not used in P52.Christopher M. Tuckett, ‘P52 and Nomina Sacra’, NTS 47 (2001) 544–8. I would like to call attention here to several factors which have a bearing on the question and which I believe balance the issue, or perhaps even tip the scales of probability a bit the other way.